2021
DOI: 10.3390/ijms222212252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cold Atmospheric Plasma on Epigenetic Changes, DNA Damage, and Possibilities for Its Use in Synergistic Cancer Therapy

Abstract: Cold atmospheric plasma has great potential for use in modern medicine. It has been used in the clinical treatment of skin diseases and chronic wounds, and in laboratory settings it has shown effects on selective decrease in tumour-cell viability, reduced tumour mass in animal models and stem-cell proliferation. Many researchers are currently focusing on its application to internal structures and the use of plasma-activated liquids in tolerated and effective human treatment. There has also been analysis of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 267 publications
0
15
0
Order By: Relevance
“…[15,38] In different medical fields, like surface decontamination from microorganisms, CAP has demonstrated remarkable clinical or preclinical potential. [1,39] Another useful application of CAP is dermatological therapy, which can improve skin rejuvenation and promote effective wound healing. With almost no impact on healthy cells, CAP in oncology has shown potential anticancer effects against a wide range of tumor cell lines and tumor tissues in animal models.…”
Section: Biomedical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…[15,38] In different medical fields, like surface decontamination from microorganisms, CAP has demonstrated remarkable clinical or preclinical potential. [1,39] Another useful application of CAP is dermatological therapy, which can improve skin rejuvenation and promote effective wound healing. With almost no impact on healthy cells, CAP in oncology has shown potential anticancer effects against a wide range of tumor cell lines and tumor tissues in animal models.…”
Section: Biomedical Applicationmentioning
confidence: 99%
“…Research is focused on discovering alternative therapies that can be combined with alreadyeffective treatments to improve results for OSCC patients. [17,39,110] Several modalities of cell death, including apoptosis, necrosis, necroptosis, autophagy, and pyroptosis, can be therapeutically targeted for the treatment of cancer cells. [111] CAP treatment raises intracellular ROS, which can impact various elements in the signaling of tumor cell death.…”
Section: Oncologymentioning
confidence: 99%
“…Importantly, it was demonstrated that CAP could be used to modify the human epigenome, with most reports focusing on DNA methylation, histone methylation, and histone acetylation [ 135 ]. Through pyrosequencing and whole-genome methylation microarray analysis, Park et al reported the effect of CAP in triggering hypomethylation of a specific CpG site of Alu from 23.4 to 20.3% in MDAMB231 TNBC cells [ 136 ].…”
Section: Combining Hdac Inhibitors With Cold Atmospheric Plasma Provides Novel Onco-therapeutic Opportunitiesmentioning
confidence: 99%
“…To date, plasma technology has been utilized mainly in the field of engineering (plasma etching and nuclear fusion), which utilizes high-energy plasmas [ 39 , 40 ]. However, in recent years, considerable resources have been directed toward analyzing the potential biological applications of plasma, especially in innovative medical treatments [ 41 , 42 , 43 ]. Currently, plasma sterilization is becoming increasingly commercially available and constitutes the main purpose of plasma use in the medical field [ 22 ].…”
Section: Fundamentals Of Plasmamentioning
confidence: 99%